PENILAIAN STATUS KOAGULASI DAN PROFIL KAROTIS SEBAGAI KOMPLIKASI SEREBROVASKULAR PADA TUMOR SUSUNAN SARAF PUSAT - Astri Budikayanti*, Teguh AS Ranakusuma*, Mursyid Bustami*, Joedo Prihartono** (Neurona Majalah Kedokteran Neuro Sains, 2009)
CAN CAUSE A DISTURBANCE IN HAEMOSTASIS AND ACTIVATE THROMBOSES MECHANISM WHICH INFLUENCED ALL THE VIRCHOWS TRIAD HYPERCOAGUABILITY CHANGES OF BLOOD FLOW AND ENDOTHELIAL CELL DAMAGE CHANGES OF HAEMOSTASIS HAPPEN IN MORE THAN 90 OF ALL CANCER AND OFTEN INFLUENCE BRAIN CIRCULATION SYSTEM WHICH CAUSED CEREBROVASCULAR COMPICATION